Microstructure, optical and photocatalytic properties of MgO nanoparticles - Balakrishnan, G.; Velavan, R.; Mujasam Batoo, Khalid; Raslan, Emad H. (Results in physics, 2020)
•MgO nanoparticles are successfully synthesized using solution combustion method.•MgO nanoparticles with the crystallite size of ~27 nm are prepared by controlling the process parameters.•The photocatalytic studies indicated the 75% degradation efficiency after 120 min UV irradiation. The present work is focused on the synthesize of MgO nanoparticles using combustion method. The magnesium nitrate is used as a precursor with urea as a fuel. The precursor material is dissolved in 50 ml DI water along with the fuel and the solution is heated at 80 °C for 2 h. Then, the solution is transferred to crucible and kept it in the temperature of 500 °C. The as-synthesized MgO nanopowders are analyzed using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy (FESEM), photoluminescence (PL) and photocatalytic studies. The XRD results of MgO nanoparticles indicated the cubic structure with the crystallite size of 27 nm. The FESEM studies indicated the formation of MgO crystallites in spherical shape. In addition, MgO nanoparticles are porous and agglomerated. PL spectrum of MgO materials exhibit emission peaks, which indicates the occurrence of band to band transition with the bandgap of 2.9 eV. The photocatalytic degradation of methylene blue dye is evaluated using the as-prepared MgO nanoparticles under UV light. The photocatalytic studies indicate the 75% degradation efficiency of the catalyst after 120 min irradiation. Hence, the MgO Nanoparticles (NPs) can be used for the treatment of effluents from the dye industries.